Opuntia Ficus Indica's effect on heart-rate variability in high-level athletes - Schmitt, L.; Fouillot, J.-P.; Nicolet, G.; Midol, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2008)
Opuntia ficus indica (OFI) has many physiological effects, but a relationship between OFI and heart-rate variability (HRV) has never been established. The aim of this study was to describe the effects of a diet supplement of OFI on HRV in athletes. The first day, heart rate (HR) was measured at rest in supine (SU) and standing (ST) positions to analyze HRV in 10 athletes, followed by a randomized assignment to an OFI (5) or placebo (5) group. The next day, the athletes repeated the HRV test. One month later the crossover protocol was applied. In OFI, the high-frequency-activity HFSU (1,773 ± 2,927 vs. 5,856 ± 8,326 ms2, p < .05), HFST (295 ± 313 vs. 560 ± 515 ms2, p < .05), and low-frequency LFU (1,621 ± 1,795 vs. 6,029 ± 9,007 ms2, p < .01) increased. HRSU (66 ± 13 vs. 57 ± 11 beats/min, p < .01) and HRST (87 ± 11 vs. 76 ± 9 beats/min, p < .01) decreased. A diet supplement of OFI increases HF and LF activities and decreases HR.